2015
DOI: 10.7717/peerj.1500
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of progressive sit-to-stand training among older hospitalized patients

Abstract: Background. In older patients, hospitalization is associated with a decline in functional performance and loss of muscle strength. Loss of muscle strength and functional performance can be prevented by systematic strength training, but details are lacking regarding the optimal exercise program and dose for older patients. Therefore, our aim was to test the feasibility of a progression model for loaded sit-to-stand training among older hospitalized patients.Methods. This is a prospective cohort study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 71 publications
5
23
0
8
Order By: Relevance
“…The present authors found the framework of Bowen et al (2009) for assessing feasibility also to be applicable regarding intellectual disability-care; it confirmed findings of previous studies on health interventions in patients with advanced, incurable diseases and their caregivers, in older hospitalized patients, and in children with autism (Bowen, Briant, Harris, Hannon, & Buchwald, 2015;Cermak et al, 2015;Pedersen et al, 2015;Siemens et al, 2015). Moreover, the present authors were able to apply all five aspects of Bowen's framework, whereas the previous studies usually addressed only some of them.…”
Section: Discussionsupporting
confidence: 87%
“…The present authors found the framework of Bowen et al (2009) for assessing feasibility also to be applicable regarding intellectual disability-care; it confirmed findings of previous studies on health interventions in patients with advanced, incurable diseases and their caregivers, in older hospitalized patients, and in children with autism (Bowen, Briant, Harris, Hannon, & Buchwald, 2015;Cermak et al, 2015;Pedersen et al, 2015;Siemens et al, 2015). Moreover, the present authors were able to apply all five aspects of Bowen's framework, whereas the previous studies usually addressed only some of them.…”
Section: Discussionsupporting
confidence: 87%
“…A 12‐month pilot study of the Johns Hopkins inpatient mobility program found more days of ambulation, increases in the proportion of individuals whose mobility levels improved over their hospital stay, and shorter hospital stays in individuals participating in the program . A cohort study demonstrated the feasibility of the SIT to STAND program, which employs a progressive model of loaded sit‐to‐stand exercises to prevent loss of muscle strength is hospitalized men . This program has not been tested in a randomized controlled trial.…”
Section: The Whatmentioning
confidence: 98%
“…43 A cohort study demonstrated the feasibility of the SIT to STAND program, which employs a progressive model of loaded sit-to-stand exercises to prevent loss of muscle strength is hospitalized men. 44 This program has not been tested in a randomized controlled trial.…”
Section: The Whomentioning
confidence: 99%
“…The randomized controlled design is the gold standard for investigating effects of interventions, but often results cannot be generalized to the real‐world clinical environment because only a small proportion (typically 10%‐15%) of the eligible patients are included …”
Section: Introductionmentioning
confidence: 99%
“…25 The randomized controlled design is the gold standard for investigating effects of interventions, but often results cannot be generalized to the real-world clinical environment because only a small proportion (typically 10%-15%) of the eligible patients are included. 26,27 The present study is a pragmatic observational study at ward level investigating the results of an increased focus on ambulation in combination with an exercise program on functional performance (mobility and muscle strength) in geriatric patients during hospital admission. We hypothesized that increased physical activity would result in greater improvements in physical performance and shorter length of stay compared to the conventional care.…”
Section: Introductionmentioning
confidence: 99%